CHARACTERIZATION OF LOW RESISTIVITY PAY ZONE COMBING ELASTIC VELOCITIES AND ELECTRICAL MEASUREMENT WITH ROCK PROPERTIES ANALOGUE ON SOME SEDIMENTARY ROCKS OF GUNUNG SEMANGGOL FORMATION - Wole , Moses Wani Paul (Universiti Teknologi PETRONAS, 2015)
This paper presents and discusses the problems of low resistivity low contrast pay zone in clastic reservoirs of ‘X’ field, Malay basin. In particular, it used Semanggol formation samples as rock properties analogue for elastic and electrical resistivity of ‘X’ field. In Malay basin, low resistivity low contrast zone is found within thinly laminated sand-shale sequences and bioturbated sandstone. In addition, LRLC zone is characterized by low resistivity of 2-6 ohm-m, a value closed to that of fresh formation water (1-2 ohm-m) in Malay basin. The main problems faced by interpreters in analyzing low resistivity low contrast zones in Malay basin are: low resistivity pay zones contain high volume of capillary bound water which makes it difficult to accurately determine the water-cut off values. In addition, low resistivity pay zones are not noticeable and easily bypassed due to; insufficient conventional logging tools and formation evaluation techniques. Geologically, low resistivity low contrast zone exist in ‘X’ field, as result of high amount of bioturbated sand-shale sequence in conjunction to high cation exchange capacity. Therefore, to solve these problems, this research measured porosity (ɸ), permeability (K), elastic properties (VP, Vs & Poisson ratio) and electrical properties of sandstone samples from Semanggol formation as analogue to rock properties of ‘X’ field in Malay basin. In addition, a synthetic core plug is created to model the condition of bioturbated sand of ‘X’ field, Malay basin. This study also interpreted logs from ‘X’ field (SPT-03 and SPT-08 well logs) and estimated the rock physics model that fits low resistivity low contrast pay zone condition in X-field, Malay basin. The result from this research serves to provide better understanding of low resistivity pay zone in ‘X’ field, Malay basin through integration of log interpretation and lab measurement of rock properties.